reply letter to Reply letter to: Retrograde Intrarenal Surgery vs. Percutaneous Nephrolithotomy vs. Extracorporeal Shock Wave Lithotripsy for Lower Pole Renal Stones 10-20 mm : A Meta-analysis and Systematic Review: stone treatment for Lower Pole Renal Stones 10-20 mm - Cubuk, Alkan; Özkaptan , Orkunt; Sahan, Ahmet (Urology Journal, 2021)
We read the article entitled ‘’Retrograde Intrarenal Surgery vs. Percutaneous Nephrolithotomy vs. Extracorporeal Shock Wave Lithotripsy for Lower Pole Renal Stones 10-20 mm: A Meta-analysis and Systematic Review’’ published in Urology Journal (1). The topic is still hot in urology regarding lower pole kidney stones in 10-20 mm diameters. Although extracorporeal shock wave lithotripsy (ESWL), retrograde intrarenal surgery (RIRS) and percutaneous nephrolithotomy (PCNL) are the available options for the patients with lower pole renal stones 10-20 mm diameter, the decision making among the methods is still controversy. This manuscript is valuable in this regard. At the present manuscript, the authors prepared a very comprehensive meta-analysis of existing evidence to quantify and compare the safety and efficacy of PCNL, RIRS and ESWL for lower pole renal stones 10-20mm. They emphasized the longer operative time of PCNL and RIRS compared to ESWL. They also reported a higher stone-free rate, the lower retreatment rate and auxiliary procedure following PCNL with the longest hospital stay for PCNL. When it comes to ESWL, the lowest SFR, the higher retreatment rate and auxiliary procedure rate, but a shorter operative time and the shortest hospital stay was reported. The authors indicated stone to skin distance (SSD) as an unfavourable factor for ESWL. This issue is also reported in current literature. SSD was calculated by measuring the distance from the stone to the skin in three angles (0°, 45° and 90°) and the cut-off value for SWL failure was reported in a wide-scale from 100 mm to 119 mm(2,3). At the present study, the authors presented 10 mm as a predictive value for the criteria of SWL failure. This statement seems to be not correct totally also 10 mm is an impossible value for SSD. In our opinion, it was caused by a misspelling, and a correction may be informative for the readers.